The Impact of an Intervention Taught by Trained Teachers on Childhood Fruit and Vegetable Intake: A Randomized Trial. (12th January 2012) - Rosário, Rafaela; Araújo, Ana; Oliveira, Bruno; Padrão, Patrícia; Lopes, Oscar; Teixeira, Vítor; Moreira, André; Barros, Renata; Pereira, Beatriz; Moreira, Pedro
Abstract : Our study aimed to assess the impact of a six-months nutrition program, taught by trained teachers, on fruit and vegetable consumption among children in grades 1 to 4. Four hundred and sixty-four children (239 female), 6 to 12 years old, from seven elementary schools were assigned to this randomized trial. Teachers were trained by researchers over six months, according to the following topics: nutrition, healthy eating, and strategies to increase physical activity. After each session, teachers were encouraged to develop activities in the classroom on the topics learned. Children's sociodemographic, anthropometric, dietary, and physical activity data were assessed at baseline and at the end of the intervention. The effect sizes ranged between small (Cohen'sd = 0.12 on "other vegetables") to medium (0.56 on "fruit and vegetable"), and intervened children reported a significantly higher consumption of vegetables and fruit. Interventions involving trained teachers offer promise to increase consumption of fruit and vegetable in children.